The renovationist movement in the Tula diocese (1922–1927) - Evseev Nikolay, Priest (Вестник Свято-Филаретовского института)
The article provides an analysis of the rise, development, and fall of the renovationist movement within the Tula diocese of the Russian Orthodox Church. It investigates the reasons behind the emergence of this schism and its unique characteristics in the Tula region. The main phases of the renewalist movement, its leading figures, support networks, and potential future developments are examined. Finally, the article concludes with a discussion of the causes behind the decline and demise of renovationism within the Tula diocese. In the Tula diocese, the renovationist movement quickly gained control of the diocese. Bishop Vitaly of Epiphany (Vvedensky) managed to give the renovationist administration of the Tula diocese a semblance of legitimacy as the chairman of the Diocesan Council. However, another vicar of the Tula diocese, Bishop Ignatius of Belevsky (Sadkovsky) refused to recognize the authority of the new church and, on the basis of his vicariage and the Belevsky Spaso-Preobrazhensky Monastery, created a community that remained loyal to His Holiness Patriarch Tikhon. This community was known as the “Belevskaya Autocephaly” in the renovation periodicals. The community was officially dissolved in 1923, but it continued to exist secretely until the late 1930s when its members were arrested and executed. The Renovationist movement continued to be active until the end of the 1920s, but then began to decline due to changes in government and party policies regarding religion.